2017
DOI: 10.15403/jgld.2014.1121.263.pak
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Th17-Associated Interleukins and Autoimmune Phenomena are Associated with the Degree of Liver Damage in Alcoholic Liver Disease

Abstract: Background & Aims: Recent reports suggest an involvement of Th17 responses in inflammatory and autoimmune reactions in alcoholic liver disease (ALD). Our study aimed to assess serum levels of Th17-interleukins in ALD with regard to the frequency of liver-specific autoantibodies and degree of liver damage.Methods: Ninety-five patients with ALD were enrolled. Serum concentrations of IL-17F, IL-17A, IL-22 were assessed by ELISA. The presence of autoantibodies AMA-M2, SLA/LP, LKM-1, LC1, anti-F-actin, anti-des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Mechanistically, it was shown that alcohol increased mitochondrial double-stranded RNA in hepatocyte-derived extracellular vesicles that signal to activate Kupffer cells to produce IL-1β, subsequently increasing IL-17 production in γδ T cells [41]. Similarly, in people with ARLD, serum IL-17F was significantly increased and, together with IL-22, was associated with a higher Model For End-Stage Liver Disease (MELD) score [42]. Moreover, Treg cells decreased during alcohol-related hepatitis [43].…”
Section: Livermentioning
confidence: 99%
“…Mechanistically, it was shown that alcohol increased mitochondrial double-stranded RNA in hepatocyte-derived extracellular vesicles that signal to activate Kupffer cells to produce IL-1β, subsequently increasing IL-17 production in γδ T cells [41]. Similarly, in people with ARLD, serum IL-17F was significantly increased and, together with IL-22, was associated with a higher Model For End-Stage Liver Disease (MELD) score [42]. Moreover, Treg cells decreased during alcohol-related hepatitis [43].…”
Section: Livermentioning
confidence: 99%
“…In this context, alcohol consumption induces hepatotoxicity through intermediaries of ethanol metabolism, or by generating different mediators of the inflammatory response, like products of the oxidative stress response or proinflammatory cytokines secreted by liver Kupffer cells, such as TNF-α ( 103 ). Serum concentrations of both IL-17 cytokine protein isoforms, together with IL-22 levels, have been proposed as correlates of liver damage progression in ALD ( 86 ). Moreover, high-IL-22 levels seem to be a good prognostic marker ( 87 ).…”
Section: Il-20 Cytokine Family In Aldmentioning
confidence: 99%